Development of a Process for Polyphenol Extraction and the Production of a Functional Powder for Food Fortification - Monica Macaluso; Nicola Mercanti; Ylenia Pieracci; Andrea Marianelli; Giulio Scappaticci; Andrea Fratacci; Cristiano Nicolella; Angela Zinnai (Applied Sciences)
The valorisation of co-products from food supply chains is consistent with the objectives of the national recovery and resilience plan (NRRP), which favours issues relating to the “green revolution and ecological transition”. The nutraceutical characteristics (antimicrobial, antiviral, anti-cancer, etc.) of grape pomace extracts are due to the presence of polyphenols. The objective of the following research was to develop an innovative extraction process in order to produce a special powder with high technological and nutraceutical value (polyphenols). For the experimentation, red grape pomace from Cabernet Sauvignon grapes was used. The first phase of the experimentation allowed the development of the extraction methods; the second involved the use of a pilot system for the extraction, filtration, and distillation phases. The result obtained is a powder with compositional characteristics suitable for the fortification of alcoholic and non-alcoholic food matrices, due to its colouring and antioxidant and nutraceutical properties.